Exploring the Conceptual Expansion within the Field of Organizational Behavior: Organizational Climate and Organizational Culture - Willem Verbeke; Marco Volgering; Marco Hessels (Tinbergen Institute, 1996)
Developments within social and exact sciences take place because scientists engage in scientificpractices that allow them to further expand and refine the scientific concepts within theirscientific disciplines. There is disagreement among scientists as to what the essential practicesare that allow scientific concepts within a scientific discipline to expand and evolve. One grouplooks at conceptual expansion as something that is being constrained by rational practices. Anothergroup however suggests that conceptual expansion proceeds along the lines of ?everything goes.'Thegoal of this paper is to test whether scientific concepts expand in a rational way within the fieldof organizational behavior. We will use organizational climate and culture as examples. The essenceof this study consists of two core concepts: one within organizational climate and one withinorganizational culture. It appears that several conceptual variations are added around these coreconcepts. The variations are constrained by rational scientific practices. In other terms, there isevidence that the field of organizational behavior develops rationally.
Keywords: 330; Organisationstheorie; Theorie